2022
DOI: 10.3389/fpsyg.2022.792224
|View full text |Cite
|
Sign up to set email alerts
|

Positive Development Based on the Teaching of Personal and Social Responsibility: An Intervention Program With Institutionalized Youngsters

Abstract: From the standpoint of the school settings, sport participation constitutes a key strategy concerning the manifestation of positive behaviors that result from the development of personal and social responsibility. Based on the TPSR model, the goal of this study was to evaluate the effects of an intervention geared toward teaching life skills through sport to youngsters who had been committed. The participants were evaluated before and after the intervention. After the initial evaluation, they were randomly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…It is noteworthy that this methodology has not only shown very favorable results in psychomotor [46] and psychological aspects such as motivation and self-efficacy in exercise [47], but researchers such as Melero-Cañas et al [65] analyzed the application of the TPSR in relation to the physical condition of Secondary school students and also improvements with a healthy lifestyle. The intervention implemented by Martins et al [66] demonstrated that sport represents a unique opportunity within the educational process to establish values, beliefs, attitudes, and practical habits of relationships and cooperation that generate social responsibility in youngsters. Furthermore, Carreres-Ponsoda et al [67] conclude that the TPSR model has the potential to be adapted and implemented also with flexibility in youth sport competition contexts in order to improve personal and social responsibility, prosocial behavior and self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that this methodology has not only shown very favorable results in psychomotor [46] and psychological aspects such as motivation and self-efficacy in exercise [47], but researchers such as Melero-Cañas et al [65] analyzed the application of the TPSR in relation to the physical condition of Secondary school students and also improvements with a healthy lifestyle. The intervention implemented by Martins et al [66] demonstrated that sport represents a unique opportunity within the educational process to establish values, beliefs, attitudes, and practical habits of relationships and cooperation that generate social responsibility in youngsters. Furthermore, Carreres-Ponsoda et al [67] conclude that the TPSR model has the potential to be adapted and implemented also with flexibility in youth sport competition contexts in order to improve personal and social responsibility, prosocial behavior and self-efficacy.…”
Section: Discussionmentioning
confidence: 99%